2012
DOI: 10.2147/dmso.s35434
|View full text |Cite
|
Sign up to set email alerts
|

Association of ADIPOQ +45T>G polymorphism with body fat mass and blood levels of soluble adiponectin and inflammation markers in a Mexican-Mestizo population

Abstract: PurposeObesity is a disease with genetic susceptibility characterized by an increase in storage and irregular distribution of body fat. In obese patients, the decrease in the Adiponectin gene (ADIPOQ) expression has been associated with a systemic low-grade inflammatory state. Our aim was to investigate the relationship between ADIPOQ +45T>G gene simple nucleotide polymorphism (SNP rs2241766) with serum adiponectin (sAdiponectin), distribution of body fat storage, and inflammation markers.Subjects and methodsI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…It has been reported that SNP +45 T > G in the adiponectin gene could affect the expression of adiponectin by influencing adiponectin mRNA processing or stability [ 21 ]. It has also been reported that SNP +45 T > G in the adiponectin gene has an association with circulating levels of adiponectin [ 28 , 30 ]. However, our results in accordance with data from other studies [ 31 ] showed that there are no association between circulating level of adiponectin, and SNP +45 T > G genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that SNP +45 T > G in the adiponectin gene could affect the expression of adiponectin by influencing adiponectin mRNA processing or stability [ 21 ]. It has also been reported that SNP +45 T > G in the adiponectin gene has an association with circulating levels of adiponectin [ 28 , 30 ]. However, our results in accordance with data from other studies [ 31 ] showed that there are no association between circulating level of adiponectin, and SNP +45 T > G genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…A variant of ADIPOQ -rs2241766 G/T was reported to be associated with adiponectin level [14], [35]. Research showed that this synonymous mutation may affect steady-state mRNA levels by altering RNA splicing or stability [42], suggesting an allele-specific differential expression of adiponectin.…”
Section: Discussionmentioning
confidence: 99%
“…Guzman-Ornelas et al . [ 23 ] evaluated the same gene polymorphism (rs2241766) as the one we studied, and did not observe any relationship between this polymorphism and adiponectin levels in Mexican-Mestizo individuals. In our study, we also found no difference in ADIPOQ ; rs2241766 gene polymorphism frequency between the 2 studied groups.…”
Section: Discussionmentioning
confidence: 96%